Hakekat Cinta dan Perannya bagi Etika Humanistik Erich Fromm - Sonia Visita Here (Ridwan Institute, 2021)
This study aims to determine how Erich Fromm's views on love, as well as to see the position of love in the whole building of Erich Fromm's Humanistic Ethics, especially in the social life of modern society today. The research method used to achieve these goals is literature study. Erich Fromm has a unique view of love. Love according to Erich Fromm is art. The art of love is manifested in active actions and is fully recognized by humans as subjects. Erich Fromm's view is his criticism of society who misunderstands love. This misunderstanding causes love to fail to become a way out of human alienation. People during Erich Fromm's time practiced love passively, namely positioning themselves and others as objects of love. More or less the same thing is still experienced by modern society today. In his ethics, Erich Fromm is of the view that humans must go through a harmonious individuation process so that they can achieve a productive character. This productive human character is capable of being the real subject or actor in the act of thinking, working, and loving. In modern times, the use of the internet in all sides of people's lives creates both convenience and difficulty for humans to become productive individuals so that they can become artists of love.